Efektifitas Metode Mind Mapping Dengan Media Gambar Terhadap Hasil Belajar Pkn Kelas Vi Materi Organisasi Negara-Negara Asia Tenggara (Asean) Di SDN Bancaran 2 Bangkalan - Alawiyah , Sulfania; Ernawati, Ernawati; Indriani, Dian Eka (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2023)
This research was carried out with the aim of analyzing the effectiveness of the Mind Mapping Method with Media Pictures on Pkn Class VI Learning Outcomes on the Organization of Southeast Asian Nations (ASEAN) material at SDN Bancaran 2. The research methodology used descriptive analysis with a quantitative approach. Descriptive analysis is a research method by collecting data in accordance with the actual data then compiled, processed and analyzed to be able to provide an overview of the existing problems. Based on the results of the analysis above regarding the comparison of data on the results of the Civics learning questionnaire before and after being treated, it shows that the results of the Civics learning questionnaire increased after being treated through the Mind Mapping methode. The average result of the pretest before being given treatment got an average value of 64.00 while the average post-test result got an average value of 84.00. Based on the results of data analysis and discussion, it can be concluded that PKN learning using the Mind Mapping method for class VI students at SDN Bencaran 2 Bangkalan is effective